Ancient Egyptian mummy genomes suggest an increase of Sub-Saharan African ancestry in post-Roman periods - Verena J. Schuenemann (Nature Portfolio, 2017)
Archaeological and historical records had shown ancient Egypt before and after Ptolemaic and Roman periods to be a hub of human migration and exchange. Here, Schuenemann and colleagues analyse ancient mitochondrial and nuclear DNA to investigate the genetic history of Egypt.